Proline-catalyzed sequential syn-mannich and [4+1]-annulation cascade reactions to form densely functionalized pyrrolidines - Aher, Ravindra D.; Kumar, B. Senthil; Sudalai, Arumugam (Journal of Organic Chemistry, 2015)
A highly efficient one-pot [4 + 1]-annulation process for the asymmetric synthesis of densely functionalized pyrrolidine derivatives is described. The in situ generated syn-Mannich adduct obtained via proline catalysis acts as a four-atom component, and Coreys sulfur ylide or ethyl bromoacetate acts as a one-atom carbon source to construct pyrrolidine units in a highly enantio- and diastereoselective manner.